Chronic Stress and Moral Decision-Making: An Exploration With the CNI Model - Zhang, Lisong; Kong, Ming; Li, Zhongquan; Zhao, Xia; Gao, Liuping (Frontiers in Psychology, 2018)
Stress is prevalent in our daily life, and people often make moral decision-making in a stressful state. Several studies have indicated the influence of acute stress on moral decision-making and behavior. The present study extended the investigation to chronic stress, and employed a new approach, the CNI model, to add new insights regarding the mechanism underlying the association between chronic stress and moral decision-making. A total of 197 undergraduates completed the Perceived Stress Scale and made moral decision-making on a series of deliberately designed moral dilemmas. The results indicated that the high-stress group (one standard deviation above the mean) preferred more deontological options than the low-stress group (one standard deviation below the mean). Process-dissociation analysis revealed that the two groups had differences on deontological inclinations but not on utilitarian inclinations. And CNI model analyses suggested that the high-stress group showed a stronger general preference for inaction than the low-stress group did, but there were no significant differences in sensitivity to consequences or sensitivity to moral norms between the two groups. Finally, the implications of our findings were discussed.